2017
DOI: 10.7150/thno.15712
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Imaging of Myocardial Inflammation in Myocarditis using 68Ga-tagged Mannosylated Human Serum Albumin Positron Emission Tomography

Abstract: The diagnosis of myocarditis traditionally relies on invasive endomyocardial biopsy but none of the imaging studies so far are specific for infiltration of the inflammatory cells itself. We synthesized 68Ga-2-(p-isothiocyanatobenzyl)-1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) mannosylated human serum albumin (MSA) by conjugating human serum albumin with mannose, followed by conjugation with NOTA and labeling it with 68Ga. The efficacy of 68Ga-NOTA-MSA positron emission tomography (PET) for imaging myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 40 publications
0
29
1
Order By: Relevance
“…), which is about 20-fold lower than that seen with [ 99m Tc]Tc(CO) 3 -anti-MMR-sdAb and 10-fold lower than with the here presented [ 68 Ga]Ga-NOTA-anti-MMR-sdAb [11]. Similar lower kidney retention for 18 Flabeled sdAb has also been reported for anti-HER2, although [13][14][15]. Depending on the chemical structure created, different catabolites will be produced in the kidney cells, with some 18 F-catabolites clearing faster from kidneys.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…), which is about 20-fold lower than that seen with [ 99m Tc]Tc(CO) 3 -anti-MMR-sdAb and 10-fold lower than with the here presented [ 68 Ga]Ga-NOTA-anti-MMR-sdAb [11]. Similar lower kidney retention for 18 Flabeled sdAb has also been reported for anti-HER2, although [13][14][15]. Depending on the chemical structure created, different catabolites will be produced in the kidney cells, with some 18 F-catabolites clearing faster from kidneys.…”
Section: Discussioncontrasting
confidence: 55%
“…Uptake in extra-tumoral MMR-expressing organs, such as the liver, spleen, lymph nodes, and bone, is slightly higher for the 68 Ga-compound when compared to the 18 F version, but substantially lower than what was observed for the 99m Tc compound. These differences may be due to different radiochemistry methods or differences in apparent molar activity (70.1, 31.5, 10.1 GBq/μmol for 99m Tc, 68 Ga, 18 F, respectively (injection time)) [11]. Kidney uptake was also different for the three variants, with the lowest value obtained for the [ 18 F]FB-anti-MMR-sdAb (7.98 ± 0.86 %IA/g at 3 h p.i.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…et al suggested that a new 68 Ga-NOTA-MSA PET tracer which has the affinity with macrophage and originally designed for visualization of the lymph nodes, could be used to detect inflammatory infiltrates in the myocardium [85]. In this study the authors used a model of myocarditis in mice, while the presence of inflammation was verified at the end of the PET scan by histological, immunohistochemical and immunofluorocene methods.…”
mentioning
confidence: 99%